Implementasi Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (Implementation of Law Number 12 of 2022 on Criminal Acts of Sexual Violence) - Hairi, Prianter Jaya; Latifah, Marfuatul (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2023)
Since the promulgation of Law Number 12 of 2022 of Criminal Acts of Sexual Violence (TPKS Law), the incidence of sexual violence remains alarmingly high throughout Indonesia. Moreover, the tactics employed are continually evolving. It is believed that the TPKS Law has not been optimally and uniformly enforced by law enforcement officers (APH). This paper delves into various regulations related to sexual violence across different laws and examines them more thoroughly in light of the obstacles hindering the implementation of the TPKS Law. Therefore, this paper aims to provide an overview of the regulation of criminal acts of sexual violence and offer recommendations to the government to promote the optimal enforcement of this law. This study adopts a normative legal research approach or doctrinal research. The analysis reveals that two essential steps are required: the issuance of all implementing regulations for the TPKS Law and the targeted dissemination of information, particularly to all stakeholders who are users of the TPKS Law, notably APH, and the general public. This ensures that the TPKS Law’s deterrent effect is increasingly felt. AbstrakSemenjak Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (UU TPKS) diundangkan, angka tindak pidana kekerasan seksual masih tinggi di seluruh Indonesia. Tidak hanya itu, modus operandi yang digunakan juga semakin berkembang. UU TPKS dianggap belum diterapkan secara optimal dan merata oleh aparat penegak hukum (APH). Artikel ini membahas berbagai pengaturan terkait kekerasan seksual di berbagai undang-undang dan mengkaji lebih dalam terkait dengan kendala dalam implementasi UU TPKS. Artikel ini oleh karenanya bertujuan untuk memberikan gambaran terkait pengaturan tindak pidana kekerasan seksual dan rekomendasi kepada pemerintah untuk mendorongoptimalisasi implementasi penegakan hukum UU tersebut. Kajian ini merupakan penelitian hukum normatif atau penelitian doktrinal. Analisis menunjukkan bahwa dibutuhkan dua langkah utama, yaknipenerbitan seluruh aturan pelaksanaan UU TPKS dan pelaksanaan sosialisasi terarah, khususnya kepada seluruh pihak sebagai user dari UU TPKS, terutama APH, serta umumnya kepada masyarakat agar efek deterrence dari UU TPKS dapat semakin dirasakan.